A sudden frenzy : improvisation, orality, and power in Renaissance Italy - Coleman, James K., 1981- (Toronto Italian studies., 2022)
"In Renaissance Italy there existed a rich interplay between two cultural practices frequently regarded as entirely separate and mutually antagonistic: the humanistic study of the ancient world and ancient literature, and the oral and improvisational performance of poetry which constituted one of the most popular forms of entertainment. A Sudden Frenzy explores the development and impact of these Renaissance practices of improvisation and oral poetry. James K. Coleman shows how the confluence of humanist culture and the art of oral poetry resulted in an extraordinary turn toward improvisation and spontaneity that profoundly influenced poetry, music, and politics. By examining the culture of improvisation, this book reveals the ways in which Renaissance thinkers transcended cultural dichotomies, both in theory and in practice. Drawing on a wide range of sources, including letters, poetry, visual art, and philosophical texts, A Sudden Frenzy reveals the far-reaching and sometimes surprising ways that these phenomena shaped cultural developments in the Italian Renaissance and beyond."--